Stability assessment of high-steep cut slope debris on a landslide (Gumushane, NE Turkey) - Kaya, Ayberk; Alemdag, Selcuk; Dag, Serhat; Gurocak, Zulfu (Springer Heidelberg, 2016)
The objective of this study was to examine the effects on the stability of slope debris of planned slope excavations around the vicinity of Gumushane Imam-Hatip High School in NE Turkey. To assess the geotechnical properties of slope debris along the determined cross-sections, four exploration boreholes with a total length of 100 m were drilled and undisturbed soil samples were collected. Slope debris is composed of two soil zones and its depth varies between 15 m and 21 m. It was determined from the experimental results that the soil class of the upper zone is CL (low plasticity clay) and CH (high plasticity clay) whereas the soil class of the lower zone is SC (clayey sand) and GC (clayey gravel). Peak cohesions of the upper and lower zones were 26.3 kPa and 10.2 kPa, and their peak internal friction angles were 16A degrees and 24A degrees, respectively. Limit equilibrium (LE) analyses for the slopes were evaluated using Slide v5.0 software for the pre-excavation, post-excavation, and supported cases. The results of LE analyses showed the existence of a landslide along the SW direction; the landslide would extend to cover the whole region if the excavation were to be performed without applying engineering measures. Finally, the precautions to be taken were determined and stability analyses for the supported case were evaluated. These analyses showed that the active lateral forces applied by the proposed retaining walls to the cut slope should be 8325 and 3103 kN, respectively.
Keywords: Landslide; Slope excavation; Stability; Slope debris; Limit equilibrium analysis